2011
DOI: 10.4172/2157-7412.s11-001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental and Genetic Factors on Various Disorders and Diseases

Abstract: Both genetic and environmental factors have been implicated in the mechanism of various disorders. Epidemiological data have shown that environmental factors can also cause and/or exacerbate the pathogenesis of these diseases. However in this article, we provide a summary of evidence for environmental and genetic factors influencing the diseases. The review also incorporates the major findings categorizing the common diseases on the basis of genetic profiles and ethnic information and in establishing personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…The summarized results of parallel sampling according to the FSBI Central AHEM showed the presence of a spectrum of carcinogenic substances indoors and outdoors due to the natural air exchange and ventilation (Table 1). Based on the obtained data and taking into account the duration of a person exposure to a particular microenvironment (atmospheric air of populated areas, residential and public buildings), and the average duration of human life, the total inhaled dosage entering the human body, and the resulting individual and total carcinogenic risks were determined [11,12]. The analysis showed the presence of certain fluctuations of the risks, depending on the location of the dwelling building.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The summarized results of parallel sampling according to the FSBI Central AHEM showed the presence of a spectrum of carcinogenic substances indoors and outdoors due to the natural air exchange and ventilation (Table 1). Based on the obtained data and taking into account the duration of a person exposure to a particular microenvironment (atmospheric air of populated areas, residential and public buildings), and the average duration of human life, the total inhaled dosage entering the human body, and the resulting individual and total carcinogenic risks were determined [11,12]. The analysis showed the presence of certain fluctuations of the risks, depending on the location of the dwelling building.…”
Section: Resultsmentioning
confidence: 99%
“…Harmful chemical factors contribute to the emergence of new mutations, which is the cause of oncology and other diseases. In particular, the total number of diseases associated with genetic changes, pregnancy disorders, and development defects has increased several times within the last years [11]. Scientific studies have found a strong relationship between the environmental pollution and the frequency of prematurity, developmental defects in children, chromosomal disorders, allergic disorders, anemia, mental retardation, abnormal behavior of children, and their physical development.…”
Section: Medical and Ecological Assessment Of The Formation Of The Camentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Many published works of literature revealed that environmental pollutants may produce genetic mutations predisposing birth defects; thus, a combination of environmental and genetic factors has been suggested as the cause. (7) A multifactorial etiology of birth defects has been considered since the recognition of thalidomide as a potent human teratogen about fifty years ago. (8) Recently, an unexplained rise in the percentage of congenital defects in numerous bombed Iraqi cities was reported, and valid studies have been issued.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, debe tenerse en cuenta que algunas enfermedades son el resultado de interacciones génicas entre los factores hereditarios y ambientales y siguen un patrón de herencia complejo. 2,3 La base de datos "Mendelian Inheritance in Man (MIM)", creada por el National Center for Biotechnology Information (NCBI), agrupa diversas enfermedades de origen genético. Con la secuenciación del genoma humano, se comprobó que existen muchas variaciones interindividuales en el ADN que corresponden a variantes genéticas y que, contrariamente a las mutaciones, son muy frecuentes.…”
unclassified